Population Pharmacokinetic Study of Cefathiamidine in Infants With Augmented Renal Clearance - Du, Bin; Zhou, Yue; Tang, Bo-Hao; Wu, Yue-E; Yang, Xin-Mei; Shi, Hai-Yan; Yao, Bu-Fan; Hao, Guo-Xiang; You, Dian-Ping; van den Anker, John; Zheng, Yi; Zhao, Wei (Frontiers in Pharmacology, 2021)
Objectives: Augmented renal clearance (ARC) of primarily renally eliminated antibacterial agents may result in subtherapeutic antibiotic concentrations and, as a consequence, worse clinical outcomes. Cefathiamidine is frequently used as empirical antimicrobial therapy in children with ARC, but pharmacokinetic studies in infants are lacking. This population pharmacokinetic study in infants with ARC was conducted to determine optimal dosing regimens of cefathiamidine. Methods: The population pharmacokinetics was conducted in 20 infants treated with cefathiamidine. Plasma samples of cefathiamidine were collected using opportunistic sampling, and the concentrations were detected by UPLC-MS/MS. Data analysis was performed to determine pharmacokinetic parameters and to characterize pharmacokinetic variability of cefathiamidine using NONMEM software program. Results: The data (n = 36) from 20 infants (age range, 0.35 - 1.86 years) with ARC were fitted best with a 1-compartment model. Allometrically scaled weight and age as significant covariates influenced cefathiamidine pharmacokinetics. The median (range) values of estimated clearance and the volume of distribution were 0.22 (0.09 - 0.29) L/h/kg and 0.34 (0.24 - 0.41) L/kg, respectively. Monte Carlo simulations showed that the cefathiamidine doses of 100 mg/kg/day q12h, 50 mg/kg/day q8h and 75 mg/kg/day q6h were chosen for bacteria with MIC 0.25, 0.5 and 2 mg/L, respectively. Conclusions: The population pharmacokinetic model of cefathiamidine for infants with ARC was developed. The PTA - based dosing regimens were recommended based on the final model.